Hubungan Penolong Persalinan Terhadap Kejadian Ruptur Perenium Spontan pada Persalinan Kala II - Naomi Parmila Hesti Savitri (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Perineal rupture is one of the causes of bleeding, which occurs because the perineum is not strong enough to withstand the stretch when the fetus passes. The purpose of this study was to determine the effect of birth attendants on the incidence of spontaneous perineal rupture in the second stage of labour. The research method used in this study is observation where research is conducted without intervening in research subjects. The population in this study were all midwives who assisted spot deliveries at the Asy Safira and Mother clinics, with the sample used as a total sampling which was taken using a consecutive sampling technique based on a predetermined time. The results of the study showed that most of the position of the second stage birth attendant's hands was not in accordance with the APN of 21 people (55.3%). 50% of cases of deliveries performed with normal birth assistance resulted in grade II perineal tears. There is an effect of the position of the second stage birth attendant's hand on perineal laceration with p = 0.020. Birth attendants are expected to continue to improve their knowledge and skills in performing childbirth assistance